PENERAPAN SISTEM FULL DAY SCHOOL DI MI KOTA MALANG - Binti Masrurotul Ainiah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
The formation and development of characters from an early age is very necessary, hence the importance of education to direct student to develope positive character in both the scope of religion and nasionalism by practicing character values in daily life. One alternative for the development of students character is by implementing a full day school system which means students are involved in school activities for one full day starting at 06.45 a.m. until 3.00 p.m as has been applied at MI Khadijah Malang. This study used a method with 3 instruments, namely: interview, observation and documentation. This study also aims to discribe: 1). Character of MI Khadijah Malang students, 2). The process of carrying out a full day school in developing character at MI Khadijah, 3). Supporting and inhibiting factors in the process of implementing full day school at MI Khadijah Malang. And the result of this study showed that broadly the character of students in MI Khadijah classified as students who where easily directed and conditioned by the application of full day school, teacher will be ease to supervise and guide students in character development through habituation of activities carried out school regularly.